2019
DOI: 10.1086/701801
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Olfactory Ideophones: Reconsidering Ineffability from the Totonac-Tepehua Perspective

Abstract: Olfactory impressions are said to be ineffable, but little systematic exploration has been done to substantiate this. We explored olfactory language in Huehuetla Tepehua-a Totonac-Tepehua language spoken in Hidalgo, Mexico-which has a large inventory of ideophones, words with sound-symbolic properties used to describe perceptuomotor experiences. A multi-method study found Huehuetla Tepehua has 45 olfactory ideophones, illustrating intriguing sound-symbolic alternation patterns. Elaboration in the olfactory dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…First, odor and label pairings were fully randomized and counterbalanced across participants to avoid potential stimulus-driven biases. Each participant was randomly assigned a unique combination of pseudowords and smells to control for the potential effect of pre-existing phono-semantic associations (Nygaard, Cook, & Namy, 2009) and of sound-symbolism for smell (O'Meara, Kung, & Majid, 2019). Example configurations are available on the project website at https://osf.io/kj5sc/.…”
Section: Counterbalancing and Randomizationmentioning
confidence: 99%
“…First, odor and label pairings were fully randomized and counterbalanced across participants to avoid potential stimulus-driven biases. Each participant was randomly assigned a unique combination of pseudowords and smells to control for the potential effect of pre-existing phono-semantic associations (Nygaard, Cook, & Namy, 2009) and of sound-symbolism for smell (O'Meara, Kung, & Majid, 2019). Example configurations are available on the project website at https://osf.io/kj5sc/.…”
Section: Counterbalancing and Randomizationmentioning
confidence: 99%
“…Korean seems to be a good example, as Korean smell ideophones are reported to be primarily an extension of their taste ideophones (Rhee and Koo 2017). Huehuetla Tepehua [hueh1236] (Totonacan) ideophones are also reported to sometimes combine taste and smell reference (O'Meara et al 2019). Understanding relations between sensory modalities and how these may influence their iconic representation in ideophones is an important area for future research, and exploring these relationships will require more complex tools than a simple, linear hierarchy (as indeed Dingemanse 2012 foreshadowed).…”
Section: Theoretical Justificationmentioning
confidence: 99%
“…The case of Huehuetla Tepehua [hueh1236] (Totonacan) is a good example. Although the language has been the subject of in-depth documentation for several years, it was not until stimulus-based elicitation was used to elicit smell descriptions that a wealth of smell ideophones were discovered (O'Meara et al 2019). This highlights the value of stimulus-based elicitation for documentary research on ideophone lexicons, and incorporating stimulus-based elicitation into such research is one way to improve the reliability of the descriptive record for future scholars.…”
Section: Future Challenges: Data Comparabilitymentioning
confidence: 99%
“…Multiple accounts have been proposed to explain odor ineffability (e.g., Engen, ; Köster et al, ; Lorig, ; Olofsson & Gottfried, ; Young). However, a growing number of studies across a variety of communities demonstrates that the ability to talk about odors is strongly influenced by the rich, structured knowledge that accompanies both professional expertise (e.g., Croijmans & Majid, ; Knaapila et al, , ; Parr et al, ; Royet, Delon‐Martin, & Plailly, ; Sezille et al, ; Urdapilleta et al, ; Zucco et al, ) and entrenched cultural and linguistic practices (e.g., Floyd et al, ; Majid & Burenhult, ; Majid et al, ; O'Meara et al, ; Wnuk & Majid, ; see Majid, for a review).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of cultural convention in the domain of olfaction has been illustrated by studies showing that some languages have rich odor vocabularies; odor naming is not hard for everyone (e.g., Floyd, San Roque, & Majid, 2018;Majid & Burenhult, 2014;O'Meara, Kung, & Majid, 2019;O'Meara & Majid, 2016;Wnuk & Majid, 2014). For example, Majid and Burenhult (2014) showed that the Jahai, who live in the Malay Peninsula, can name odors as easily as they name colors.…”
Section: Introductionmentioning
confidence: 99%